2019
DOI: 10.1016/j.midw.2019.102535
|View full text |Cite
|
Sign up to set email alerts
|

Immediate, uninterrupted skin-to-skin contact and breastfeeding after birth: A cross-sectional electronic survey

Abstract: Objective: To determine the incidence of immediate, uninterrupted skin-to-skin contact and breastfeeding after birth; and which factors are associated with it. Design: Cross-sectional e-survey was developed and piloted prior to distribution. Sampling was purposive and included snowball sampling. Associations between maternity care practices and the primary outcome measure were examined using logistic regression. Setting: Australia Participants: Women who birthed a term baby within the previous three years, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A fact also observed by other studies, which revealed that women undergoing cesarean section, have almost three times the risk of not performing SCC with early initiation of breastfeeding. Newborns born by vaginal delivery were more prepared to start breastfeeding compared to those born by cesarean section, since they spent more time in early contact with the mother [10][11]19,27 . These data corroborate the findings of this research.…”
Section: /14mentioning
confidence: 99%
“…A fact also observed by other studies, which revealed that women undergoing cesarean section, have almost three times the risk of not performing SCC with early initiation of breastfeeding. Newborns born by vaginal delivery were more prepared to start breastfeeding compared to those born by cesarean section, since they spent more time in early contact with the mother [10][11]19,27 . These data corroborate the findings of this research.…”
Section: /14mentioning
confidence: 99%
“…In a study that included 1,200 mother-child binomials, SSC after birth was performed by 100% all of them (15) , contrary to this of Skin-to-skin contact between mothers and full-term newborns after birth: a cross-sectional study Kuamoto RS, Bueno M, Riesco MLG.…”
Section: Discussionmentioning
confidence: 99%
“…However, regardless of the mothers initiating early skin-to-skin contact, the duration of SSC was often shorter than the recommended 60 min. Previously it has been shown that non-urgent practices, such as weighing the baby or assisting the mother to have a shower, interrupted the continuous SSC between the mother and her infant ( Allen et al., 2019 ). Early SCC establishes a good starting point for breastfeeding as it contributes to the initiation, length, and exclusivity of breastfeeding, and increases support for better physiological stability of the infant in adapting to extrauterine life ( Moore et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%